Evaluation of the Carbon Footprint of Fresh Durian Grown in an Agroforestry System in Uttaradit Province, Thailand - Podong, Chattanong; Ulbonsook, Puttadee; Noinamsaib, Supawadee (Thai Journal of Science and Technology, 2020)
The calculation of carbon footprint (CF) as an estimate of greenhouse gas emissions is one method used to measure environmental impact. Including carbon labeling on a product informs consumers of the environmental cost of that product during every stage of its life cycle (PLC), from acquisition and processing of raw materials to manufacturing, distribution and ultimate use. The purpose of this study was to estimate the CF of durian grown within an agroforestry system, including the removal of unconsumed portions of the fruit, in Ban Dan Na Kham, Uttaradit province, Thailand. Acquiring and processing fresh durian were responsible for 0.355 kg CO2-eq and 0.00018 kg CO2-eq, respectively. Distribution of fresh durian had a CF of 0.0359 kg CO2-eq, and consumption was considered to have a CF of zero. Disposal of the inedible parts of durian constituted the largest CF component (1.9006 kg CO2-eq), almost 83 % of the total CF (2.30 kg CO2-eq) for all processes. Reducing disposal of the inedible portion of durian by selling it pre-peeled for consumers or reusing the peel for a variety of packaging purposes may help to reduce the environmental impact of fresh durian production.